2003
DOI: 10.1167/iovs.02-1084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL-4 on Conjunctival Fibroblasts: Possible Role in Ocular Cicatricial Pemphigoid

Abstract: Increased conjunctival expression of IL-4 may play an important role in the regulation of local accumulation of macrophages (by inducing m-CSF), and matrix accumulation (by inducing HSP47 and collagen) during conjunctival scarring in patients with OCP. IL-4, therefore, may augment or enhance both conjunctival inflammatory and subsequent fibrotic responses in patients with OCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Using human embryonic lung fibroblasts, it has been shown that both TGF-␤ 1 and IL-␤ 1 could induce trimer formation of heat shock transcription factor 1, which then bound to heat shock element of HSP47, resulting in increased expression of HSP47 [50]. In addition, certain other profibrogenic cytokines, including IL-4, IL-13, and connective tissue growth factor have shown to induce the expression of HSP47 [51][52][53]. Human conjunctival fibroblasts, treated with various concentrations of IL-4 [51] and IL-13 [52], could induce the expression of both HSP47 and collagens.…”
Section: Regulatory Mechanisms Of Hsp47 Expressionmentioning
confidence: 99%
“…Using human embryonic lung fibroblasts, it has been shown that both TGF-␤ 1 and IL-␤ 1 could induce trimer formation of heat shock transcription factor 1, which then bound to heat shock element of HSP47, resulting in increased expression of HSP47 [50]. In addition, certain other profibrogenic cytokines, including IL-4, IL-13, and connective tissue growth factor have shown to induce the expression of HSP47 [51][52][53]. Human conjunctival fibroblasts, treated with various concentrations of IL-4 [51] and IL-13 [52], could induce the expression of both HSP47 and collagens.…”
Section: Regulatory Mechanisms Of Hsp47 Expressionmentioning
confidence: 99%
“…4,5 These processes involve a variety of cells, signals, and soluble extracellular factors, 4 including TGF-b, platelet-derived growth factor (PDGF), TNF-a, epidermal growth factor, insulin-like growth factor (IGF)-1, interleukin (IL)-1, IL-6, IL-4, interferons, BFGF, and macrophage-colony stimulating factor (m-CSF). 4,[6][7][8] TGF-b is one of the most important profibrogenic cytokines in the proliferative phase of wound healing. TGF-b induces the differentiation of fibroblasts into myofibroblasts, which are characterized by the expression of a-smooth muscle actin (a-SMA), a high contractile capacity, and the synthesis of extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…In pemphigoid diseases, the release of some proteolytic enzymes, involved in blistering formation, was highly correlated with a set of immunoregulatory cytokines [31]; high levels of IL-4, IL-5, IL-10, IL-13, IL-17 and IFN-γ have been detected in skin lesions or sera of patients with bullous pemphigoid and especially regarding IL-4 and IL-13 for ocular cicatricial pemphigoid and for oral mucous membrane pemphigoid, confirming their presumed involvement in the cicatricial scarring process [32][33][34]. IL-13 promoted both fibroblast migration and up-regulation of the expression for major histocompatibility complex components (HLA) and for some CD proteins, so that fibroblasts may perpetuate chronic inflammation and continue fibrosis [33].…”
Section: Experimental Evidence Of the Involvement Of Upper Cluster Gementioning
confidence: 72%